Phylogenetic Diversity of Sequences of Cyanophage Photosynthetic Gene psbA in Marine and Freshwaters - Chénard, C. (American Society for Microbiology (ASM), 2008)
Many cyanophage isolates which infect the marine cyanobacteria Synechococcus spp. and Prochlorococcus spp. contain a gene homologous to psbA, which codes for the D1 protein involved in photosynthesis. In the present study, cyanophage psbA gene fragments were readily amplified from freshwater and marine samples, confirming their widespread occurrence in aquatic communities. Phylogenetic analyses demonstrated that sequences from freshwaters have an evolutionary history that is distinct from that of their marine counterparts. Similarly, sequences from cyanophages infecting Prochlorococcus and Synechococcus spp. were readily discriminated, as were sequences from podoviruses and myoviruses. Viral psbA sequences from the same geographic origins clustered within different clades. For example, cyanophage psbA sequences from the Arctic Ocean fell within the Synechococcus as well as Prochlorococcus phage groups. Moreover, as psbA sequences are not confined to a single family of phages, they provide an additional genetic marker that can be used to explore the diversity and evolutionary history of cyanophages in aquatic environments.